Step * 1 1 of Lemma inverse-of-strict-increasing-function


1. Interval
2. I ⟶ℝ
3. Interval
4. x:{x:ℝx ∈ J}  ⟶ {x:ℝx ∈ I} 
5. ∀t:{t:ℝt ∈ I} (f t ∈ J)
6. ∀x,y:{x:ℝx ∈ I} .  ((x < y)  ((f x) < (f y)))
7. ∀x,y:{t:ℝt ∈ I} .  ((x y)  ((f x) (f y)))
8. ∀x:{x:ℝx ∈ J} ((f (g x)) x)
9. {x:ℝx ∈ I} 
10. (f (g (f x))) (f x)
⊢ (g (f x)) x
BY
((BLemma `not-rneq` THENA Auto) THEN (D THENA Auto) THEN -1 THEN FHyp [-1] THEN Auto) }


Latex:


Latex:

1.  I  :  Interval
2.  f  :  I  {}\mrightarrow{}\mBbbR{}
3.  J  :  Interval
4.  g  :  x:\{x:\mBbbR{}|  x  \mmember{}  J\}    {}\mrightarrow{}  \{x:\mBbbR{}|  x  \mmember{}  I\} 
5.  \mforall{}t:\{t:\mBbbR{}|  t  \mmember{}  I\}  .  (f  t  \mmember{}  J)
6.  \mforall{}x,y:\{x:\mBbbR{}|  x  \mmember{}  I\}  .    ((x  <  y)  {}\mRightarrow{}  ((f  x)  <  (f  y)))
7.  \mforall{}x,y:\{t:\mBbbR{}|  t  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((f  x)  =  (f  y)))
8.  \mforall{}x:\{x:\mBbbR{}|  x  \mmember{}  J\}  .  ((f  (g  x))  =  x)
9.  x  :  \{x:\mBbbR{}|  x  \mmember{}  I\} 
10.  (f  (g  (f  x)))  =  (f  x)
\mvdash{}  (g  (f  x))  =  x


By


Latex:
((BLemma  `not-rneq`  THENA  Auto)  THEN  (D  0  THENA  Auto)  THEN  D  -1  THEN  FHyp  6  [-1]  THEN  Auto)




Home Index